The Effects of Occupational Health, Safety and Wellbeing on Operations and Performance at Gambia Ports Authority Mediated by Policy and Procedures. - Ceesay, Sainabou M; Badjie, Gibriel (Universitas Nusantara PGRI Kediri, 2025)
Research aim: The study aims to evaluate the effectiveness of the current Occupational Health, Safety and well-being policy of the GPA. Additionally, assessed the effects of OHS on Port Operations and Employee Performance and as well as the health hazards associated with poor Occupational Health and Safety standards. Design/Methode/Approach: A descriptive and exploratory survey design was utilized with a structured questionnaire and Likert 5- point scale to collect data. The study also utilized stratified random sampling method and drawing a sample of 210 staff from the GPA staff roll provided by Human Resources. The data was analyzed using both descriptive and structural equation modelling (SEM) techniques with help of SPSS software and SmartPLS4. Research Finding: The study found out that the current OHS policy of the GPA was effective since a significant percentage of the respondents are aware and have access to such a policy. It also indicated that implementation of OHS policy was communicated to majority of the employees. The staff also agreed that the availability of effective working conditions enhance employee performance and operational efficiency. The nature of Ports Operations indicated that the most vulnerable groups experienced workplace hazards more frequently. The perception of safety standards at the Ports Authority is generally below average. Theoretical contribution/Originality: The study has contributed to knowledge by bridging the gap in establishing the relationship of OHS on employee and organisational performance. It gave a fresh perspective on Gambia Ports operations as well as the challenges in relations with employee health, safety and well-being. Practitionel/Policy implication: The Expansion of the Port infrastructure should be expedited to provide the much-needed space and avoid the presence of health hazards associated with poor standards. The Management of GPA should organize more awareness campaigns for operational staff in order to educate them about OHS and how they can practice caution on their own. The GPA leadership should facilitate the formulation of better health and safety policies and procedures. It would also assist employees to improve their welfare and ensure a safe working environment for all. Research limitation: The study conclusions cannot be generalized as its from a single entity.